Market Situation Interpretation and Response: The Role of Cognitive Style, Organizational Culture, and Information Use - White, J. Chris; Varadarajan, P. Rajan; Dacin, Peter A. (Journal of Marketing, 2003)
Improving marketing decision making requires a better understanding of the factors that influence how managers interpret and respond to a market situation. Building on extant literature, the authors develop a model that delineates antecedents of and responses to the interpretation of a market situation. Using case-scenario methodology, the authors test the model in the context of a marketing decision (annual advertising and promotion budget recommendation) with data collected from a nationwide sample of hospital marketing executives. The results of the partial least squares analysis show that (1) cognitive style, organizational culture, and information use affect the extent to which managers perceive a given market situation as one in which they can control the outcomes of their decision; (2) the more managers perceive a situation as controllable, the more they appraise that situation as an opportunity; and (3) the more managers appraise a situation as an opportunity, the greater is the magnitude of their response.